Analysis of Mixed Marriage Law in Indonesia From the Perspective of International Civil Law Improvement - Sari, Siti Julaeha Puspika; Setiawan, Andre; Adillah, Alya Sophia; Mustapid, Hidayatul; Khairunnida, Tasya; Wijaya, Mustika Mega (Universitas PGRI Madiun, 2025)
Law Number 1 of 1974 concerning Marriage contains a section on religiosity. A man and a woman become husband and wife with the aim of realizing a happy and eternal family based on the One Almighty God. This is the definition of marriage itself. The Civil Code and the Marriage Law have different definitions of marriage: in Article 26 of the Law